Analisis Alasan Nasabah Dalam Memilih Pegadaian Syariah Sebagai Solusi Permasalahan Keuangan (Studi Kasus Produk RAHN) - Zainarti Zainarti; Muhammad Syafrizal (LPPM Universitas Labuhanbatu, 2024)
This study aims to determine and analyze the influence of promotion, loan disbursement procedure, syaria aspect, and location on the interest of customers using rahn products on syaria pawnshops. The research used quantitative research. The population in this research is all customers who used rahn products on syaria pawnshops. The technique of sampling method used convenience sampling and retrieved samples of 100 respondents. For data analysis method, using multiple linear regression analysis with SPSS. The results of this study indicated that promotion, loan disbursement procedure, syaria aspect, and location simultaneously affect the interest. Partially, the result shows that promotion, loan disbursement procedure, syaria aspect, and location have a significant effect on the interest of customers using rahn products at theÂ Kuala SimpangÂ Syariah Pawnshop Head Office